Dual-band linear polarization converter based on multi-mode metasurface - Yueyang Wu; Shengxiang Huang; Lianwen Deng; Chao Tang; Xiaohui Gao; Shuguang Fang; Lei-Lei Qiu (Results in Physics, 2022)
This paper proposes a dual-band linear polarization converter based on multi-mode metasurface. The converter consists of square-patch-resonator-based metasurface etched with cross-slot, which is beneficial to separate the degenerate modes of the patch resonator in the first band, as well as to generate additional resonant modes for the second conversion band. Different from the traditional method of using multiple resonators for dual-band polarization converters, the proposed one only utilizes one multi-mode resonator. Additionally, the two bands can be tuned relatively independently by appropriately changing the physical parameters of the resonator. To verify the design method, one sample is fabricated and measured. The proposed linear polarization converter works in the two frequency ranges of 3.16–3.52 GHz and 7.19–8.61 GHz with a polarization conversion rate (PCR) ≥ 90 %.